Assessment of Farmer’s Tree Preferences and Their Seasonal Frost Management Practices in Frost-Affected Highlands of Eastern Ethiopia - Getachew, Goremsu; Bogale, Daba; Tesfaye, Abera (Indonesian Journal of Environmental Management and Sustainability, 2023)
Deforestation, land degradation, and low survival of planted seedlings are serious problems in highland Ethiopia. To address these problems, different land management practices such as afforestation and conservation program have been implemented; however, the success to date limited due to environmental stress and insufficient post-planting care. Therefore, the objective of this study was to investigate farmer’s tree needs and their traditional knowledge of seasonal frost management practices in selected frost-affected highlands of Eastern, Ethiopia. A total of 111 households were randomly selected for interviews on farmer’s tree species preference, frost management practices, and the causes of seedling mortality in the study area. Furthermore, key informant interviews and focus group discussions were used to collect the data. Descriptive statistics were used to analyze the data. The results confirm that season frost (55.6%) followed by free grazing (22.2%), inappropriate species site match (11.1%), and inappropriate planting time (5.6%) were major causes of seedling mortality in the study area. Organic mulch, plant cover, smoking, watering, and manuring were seasonal frost management practices applied by farmer’s to enhance seedlings’ survival in the study areas. However, this indigenous knowledge should be encouraged by the government through improved research, and extension services, to enhance seedlings’ survival in the study areas as well as to introduce it in different frost-prone highlands of Ethiopia. Moreover, species such as Eucalyptus globulus’ Labill, Cupressus lusitanica Mill., Juniperus procera Hochst. ex Endl., Hagenia abyssinica a (Bruce) J.F.Gmel, and Podocarpus falcatus (Thunb.) Mirb. (syn. P. gracilior Pilg.), were suggested as frost-tolerant species in the study area. Therefore, it is recommended that planting these tree species through research and campaign is essential to reduce land degradation in the frost-affected highlands area of the country, particularly in the study area.